A Methods engineering study on the Master's Legacy - Dela Paz, Rupher; Del Rosario, Francis; Del Rosario, Ryan. (Diliman, Quezon City College of Engineering, 2000)
The Master's Legacy Inc. is one of several companies that engages with the production of religious figures and home decorations such as angels, candlesticks and the like. These items can be found at department stores, bazaars, and boutiques. Like any other company, The Master's Legacy, Inc., faces several problems and difficulties with their present system regarding operations and production. In this methods engineering study, analytical tools and experimentation were used and conducted to determine the minor and major problems the company is encountering. Examples of the tools applied are Streamline diagram, Ishikawa diagram, Root Verification Matrix. The study also made use of time study and observed the operation process. The data gathered were then relayed through different charts such as multiple activity charts, left hand right hand charts, systems and procedures charts, forms charts, etc. From the identification of the problem, analysis was conducted to determine the major problem that concerns the company. Alternatives were then generated to suggest different solutiions to minimize or eradicate the effects of these problems. Analysis of each alternative was then conducted to determine which alternatives are the most appropriate, economical and effective to be recommended. With the recommendations presented by the study, implementation strategies were also included. With the study conducted on The Master's Legacy Inc. , the authors hope that the analysis of the problem involved prone to be accurate and that recommendations presented be deliberated upon and be welcomed by the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: The Master's Legacy; House furnishings industry and trade; Systems analysis